Demand for meat in Malaysia: an application of the almost ideal demand system analysis - Baharumshah, Ahmad Zubaidi; Mohamed, Zainal Abidin (Universiti Pertanian Malaysia Press, 1993)
This article presents the estimates of the Almost Ideal Demand System (AIDS) for five meat groups in Malaysia. The linear version of the AIDS model is easily estimated using most of the available commercial computer software that have several desirable theoretical properties. The results show that own-price elasticities were negative, statistically significant, and except for chicken, in the inelastic range. In general, the cross-price elasticities were positive. The demand for pork, chicken, mutton and fish were all found to be elastic with respect to expenditure.